(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the problem of health services in Mennonite colonies during 1789 — 1917. Two stages of creation of health services in Mennonite villages are allocated by author. At the first stage, in the end of the XVIII century — in the 70-s of the XIX century, the families solved a problem of obtaining a medicalaid by their own. The second stage of development of health services began in the 80-s of the XIX century, after revising the ratio of a community to this problem, when the communal and private hospitals of colonies were established.